Masculinity and sexuality in modern Mexico - Macías-González, Víctor M.; Rubenstein, Anne (University of New Mexico Press, 2012)
In Masculinity and Sexuality in Modern Mexico, historians and anthropologists explain how evolving notions of the meaning and practice of manhood have shaped Mexican history. In essays that range from Texas to Oaxaca and from the 1880s to the present, contributors write about file clerks and movie stars, wealthy world travelers and ordinary people whose adventures were confined to a bar in the middle of town. The Mexicans we meet in these essays lived out their identities through extraordinary events--committing terrible crimes, writing world-famous songs, and ruling the nation--but also in everyday activities like falling in love, raising families, getting dressed, and going to the movies. Thus, these essays in the history of masculinity connect the major topics of Mexican political history since 1880 to the history of daily life. Part of the Diálogos Series of Latin American Studies